Light absorption and short-circuit current density in plasmonic organic solar cells containing liquid crystal and metal nanowires - Milad Soleimiani; Mohammad Javad Karimi; Hamed Rahimi (Journal of Optoelectronical Nanostructures)
In this work, a plasmonic organic solar cell consisting of the organic material P3HT:PCBM, PEDOT:PSS, nematic liquid crystal 5CB, ITO, and metal nanowires was simulated in the wavelength range of 300 to 1200 nm. The substrate and nanowires are made of chrome, copper, and aluminum metals. The refractive indices of the metals were determined from the Drude–Lorentz equation. The values of the geometrical parameters corresponding to the high absorption were calculated. The impact of the layer thicknesses and incident light angle on the short-circuit current density is investigated. The results indicate that the nanowires significantly increase the absorption of the solar cell. Results indicate that the system made of chrome material has a broadband absorption rate of over 90%. Among all the proposed structures, the chrome-based solar cell has a maximum short-circuit current density of approximately . However, this value significantly decreases for incident angles above 40 degrees.